Ultrathin carbon layer coated MXene/PBO nanofiber films for excellent electromagnetic interference shielding and thermal stability - Gong, Kaijie; Peng, Yanmeng; Liu, An; Qi, Shuhua; Qiu, Hua (Composites. Part A, Applied science and manufacturing, 2024)
In this study, a carbon layer coated MXene/poly(p-phenylene-2,6-benzobisoxazole) nanofibers (PNFs) (MXene/PNF@C) EMI shielding composite film was obtained through polymer infiltration and pyrolysis (PIP) technique. The introduction of the carbon layer improved both the electrical and thermal conductive pathways of the film leading to the enhancement of its electrical conductivity(σ), thermal conductivity coefficient (λ) and EMI shielding effectiveness (SE). Meanwhile, thermal annealing reduced the defects of PBO molecular chains and improved the mechanical properties of the composite film. When the content of MXene is 50 wt% and the thickness of the film is only 37 μm, MP50@C-400 composite film has the best comprehensive properties, with the σ, λ, specific EMI SE (SEₜ) and tensile strength is 1760 S/m, 5.64 W/(m·K), 1108.1 dB/mm and 66.8 MPa, respectively, and its weight loss is only 24.1% at 800°C. The composite film provides important application prospects in 5G communication technology, wearable equipment and artificial intelligence.